The encyclopedia of Judaism / vol. 5. Supplement II. - Neusner, Jacob, 1932-; Avery-Peck, Alan J. (Alan Jeffery), 1953-; Green, William Scott; Museum of Jewish Heritage (New York, N. Y.) (New York : Continuum, 2004)
"With more than 100 lengthy essays, this exceptional work on Judaism covers more than its historical framework. The Encyclopedia of Judaism provides complete and accurate coverage of Judaism--everything from its history, beliefs, and observances, from the beginning to modern times. It is an excellent source written by scholars."--"Outstanding Reference Sources," American Libraries, May 2001.
v. 1. A-I -- v. 2. J-O -- v. 3. P-Z -- v. 4. Supplement I -- v. 5. Supplement II
"Published in collaboration with the Museum of Jewish Heritage, New York."
Includes bibliographical references and indexes.
Also available on CD-ROM.
Keywords: Judaism -- Encyclopedias